Anethole Pretreatment Modulates Cerebral Ischemia/Reperfusion: The Role of JNK, p38, MMP-2 and MMP-9 Pathways - Nancy S. Younis; Maged E. Mohamed (MDPI AG, 2023)
Anethole (AN) is one of the major constituents of several plant oils, demonstrating plentiful pharmacological actions. Ischemic stroke is the main cause of morbidity and death worldwide, particularly since ischemic stroke therapeutic choices are inadequate and limited; thus, the development of new therapeutic options is indispensable. This study was planned to explore the preventive actions of AN in ameliorating cerebral ischemia/reperfusion-induced brain damage and BBB permeability leakage, as well as to explore anethole's potential mechanisms of action. The proposed mechanisms included modulating JNK and p38 as well as MMP-2 and MMP-9 pathways. Sprague-Dawley male rats were randomly assigned into four groups: sham, middle cerebral artery occlusion (MCAO), AN125 + MCAO, and AN250 + MCAO. Animals in the third and fourth groups were pretreated with AN 125 or 250 mg/kg orally, respectively, for two weeks before performing middle cerebral artery occlusion (MCAO)-induced cerebral ischemic/reperfusion surgery. Animals that experienced cerebral ischemia/reperfusion exhibited amplified infarct volume, Evans blue intensity, brain water content, Fluoro-Jade B-positive cells, severe neurological deficits, and numerous histopathological alterations. MCAO animals exhibited elevated MMP-9 and MMP-2 gene expressions, enzyme activities, augmented JNK, and p38 phosphorylation. On the other hand, pretreatment with AN diminished the infarct volume, Evans blue dye intensity, brain water content, and Fluoro-Jade B-positive cells, improved the neurological score and enhanced histopathological examination. AN effectively lowered MMP-9 and MMP-2 gene expression and enzyme activities and diminished phosphorylated JNK, p38. AN decreased MDA content, amplified GSH/GSSG ratio, SOD, and CAT, decreased the serum and brain tissue homogenate inflammatory cytokines (TNF-α, IL-6, IL-1β), NF-κB, and deterred the apoptotic status. This study revealed the neuroprotective ability of AN against cerebral ischemia/reperfusion in rats. AN boosted blood-brain barrier integrity via modulating MMPs and diminished oxidative stress, inflammation, and apoptosis through the JNK/p38 pathway.